Investment Utilisation, Adjustment Costs, and Technical Efficiency in Danish Pig Farms - Jakob Vesterlund Olsen; Arne Henningsen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2011)
In this paper, we present a theoretical model for adjustment costs and investment utilisation that illustrates their causes and types and shows in which phases of an investment they occur. Furthermore, we develop an empirical framework for analysing the size and the timing of adjustment costs and investment utilisation. We apply this methodology to a large panel data set of Danish pig producers with 9,281 observations between 1996 and 2008. The paper further contributes with a thorough discussion of the calculation and deflation of capital input from microeconomic data. We estimate an output distance function as a stochastic frontier model and explain the estimated technical inefficiencies with lagged investments, farm size and age of the farmer. We allow for interaction effects between these variables and derive the formula for calculating the marginal effects on technical efficiency. The results show that investments have a negative effect on farm efficiency in the year of the investment and the year after accruing from adjustment costs. There is a large positive effect on efficiency two and three years after the investment. The farmer's age and the farm size significantly influence technical efficiency, as well as the effect of investments on adjustment costs and investment utilisation. These results are robust to different ways of measuring capital.
Keywords: Q12; D22; D24; D92; 330; investment utilisation; adjustment costs; stochastic frontier analysis; technical efficiency; pig production; Denmark